2015
DOI: 10.1002/cbdv.201400055
|View full text |Cite
|
Sign up to set email alerts
|

A New DNA‐Intercalative Cytotoxic Allylic Xanthone from Swertia corymbosa

Abstract: Phytochemical investigation of the CHCl3 fraction of Swertia corymbosa resulted in the isolation of a new 3-allyl-2,8-dihydroxy-1,6-dimethoxy-9H-xanthen-9-one (1), along with four known xanthones, gentiacaulein (3), norswertianin (4), 1,3,6,8-tetrahydroxyxanthone (5), and 1,3-dihydroxyxanthone (6). Structure of compound 1 was elucidated with the aid of IR, UV, NMR, and MS data, and chemical transformation via new allyloxy xanthone derivative (2). Compounds 1-6 exhibited various levels of antioxidant and anti-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…By promoting S-phase arrest, these compounds impair DNA replication [24]. Consistently, previous evidence has indicated that xanthone derivatives may interact with DNA through intercalation, suppressing its replication in cancer cells [11,12].…”
Section: Xgac Induces Cell Cycle Arrest Apoptosis and Genotoxicity In...supporting
confidence: 54%
See 1 more Smart Citation
“…By promoting S-phase arrest, these compounds impair DNA replication [24]. Consistently, previous evidence has indicated that xanthone derivatives may interact with DNA through intercalation, suppressing its replication in cancer cells [11,12].…”
Section: Xgac Induces Cell Cycle Arrest Apoptosis and Genotoxicity In...supporting
confidence: 54%
“…Xanthones are O-heteroaromatic tricyclic scaffolds, which provide a wide range of derivatives with several biological responses, representing a privileged structure for anticancer drug development [10]. Particularly, this class of oxygen-containing heterocyclic compounds can intercalate into the base group pairs of DNA due to the appropriate planarity of the xanthone ring, causing DNA damage in cancer cells through non-covalent interaction with DNA [11,12]. In addition, the glycosidic moiety of natural glycosides of flavonoids and xanthones may exhibit biological activities that positively affect the antitumor activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Considering structural similarities among other molecules, inhibition was much stronger for those containing the C-1 allyl group ( 7 , 9b , and 11b ). The data suggest that a molecule with an allyl or substituted aryl group has better affinity for the amino acid residues of the α-glucosidase enzyme and thus enhanced bioactivity, which owes itself to π-sticking or hydrophobic effects [ 11 , 21 , 37 ], as well as interactions with the halogen atoms substituted at the phenyl groups or at the alkyl side chain [ 36 , 38 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several heterocyclic compounds containing oxygen and nitrogen are relevant for designing and developing new drugs. For instance, xanthone is a dibenzo-γ-pyrone heterocycle that has drawn the attention of researchers due to its broad spectrum of biological activity [ 8 , 9 , 10 , 11 ]. Xanthone derivatives are oxygenated heterocyclic compounds that occur as secondary metabolites in some families of higher plants (Guttiferae, Gentianaceae, Moraceae, Clusiaceae, and Polygalaceae).…”
Section: Introductionmentioning
confidence: 99%
“…It would be worthwhile to investigate medicinal plants used to treat wounds in folk medicines for the identification of new lead antimicrobial compounds. In our continuing efforts to discover new bioactive natural products from ethnomedicinal plants , we have collected stems and bark of D . staudtii from Nigeria based on its reported ethnomedicinal properties.…”
Section: Introductionmentioning
confidence: 99%